Software Design of Autocorrection Essays on the Website and Application - Novalanza Grecea Pasaribu; Menara Alif; Gelar Budiman; Fityanul Akhyar (Universitas Ahmad Dahlan, 2023)
Traditional essay assessment methods are often time-consuming and prone to subjectivity. This study proposes a novel Automated Essay Scoring (AES) system,